Rancang Purwarupa Aplikasi Pendukung Keputusan Pemilihan Jurusan Bagi Mahasiswa dengan Pendekatan Design Thinking - Michael; Charlitos, Ralfpiere; Sudiono; Thang, Susanti (Fakultas Komputer - Universitas Universal, 2021)
The purpose of this study is to design an application prototype that can help all the incoming student to know their inner self and choose the best major according to their skill. This research is a qualitative research with a Design Thinking approach. The Design Thinking approach has five stages namely emphatize, define, ideate, prototype, and test. Design Thinking Approach is an approach used to create innovation by focusing on